The Allegation of International Human Rights Treaties - Salazar Marín, Daniela (Iuris Dictio, 2017)
The ratification of international human rights treaties is considered an ordinary act of each State’s international relations. However, the denunciation of an international human rights treaty is an act of particular gravity, and therefore limited by both international law and domestic law. This essay analyzes such limits and reviews the few cases of denunciation of international human rights treaties in an effort to demonstrate that it is not a sovereign power that States can exercise without restrictions. The case of Ecuador is examined in light of the constant threats from its government to withdraw from the Inter-American Human Rights Protection System.